Rancang Sistem Informasi Sinkron Untuk Memperluas Pemasaran Dan Mengelola Transaksi: Design A Syncron Information System to Expand Marketing and Manage Transactions - Ammara Diani Yusuf; M.Fahrul Muchlis; M. Ardiansyah; Nadia Alya Putri; Zeldi Firman (LPPM Universitas Merdeka Madiun, 2024)
The importance of information systems has significantly increased in today's era of globalization, becoming a crucial prerequisite and success factor for both private and public organizations. This study aims to design a web-based information system for